Northrop Frye's notebooks for anatomy of criticism - Frye, Northrop (Frye, Northrop. Works. 1996 ;, 2007)
This fully annotated volume contains seventeen holograph notebooks, each illuminating some aspect of the grand structure that eventually emerged. Altogether, the notebooks offer an intimate picture of Frye's working process and a renewed appreciation for his magisterial accomplishment.